Types of Steering and Their Design Aspects: Jenis Kemudi dan Aspek Desainnya - Rustamov, Kamoliddin Juraboevich; Tojiev, Lazizbek Orifjonovich (Indonesian Journal of Innovation Studies, 2022)
This article provides information about steering mechanisms, their types and designs. It was also discussed in which vehicles these steering gear designs could be used.